Representation of The Meaning of The Song “Sampai Jadi Debu” By Ananda Badudu - Safitri, Laura Haris; Marwan, Iwan (Proceeding International Conference on Education, 2024)
This research aims to determine the meaning of the connotation and denotation meaning of a song entitled "Sampai Jadi Debu" by Ananda Badudu. This research attempts to describe the signs and markers of the connotation and denotation meanings in the song lyrics. This research uses a qualitative descriptive method, which aims to provide a comprehensive and in-depth picture of the object under study. The data source taken is the meaning contained in the lyrics of the song "Sampai Jadi Debu" by Ananda Badudu. The data collection used was a literature review which was carried out using the technique of reading, identifying and recording the meanings found in the song lyrics. The theory applied is Roland Barthes' semiotic theory which involves a thorough reading process of song lyrics, identifying important elements that describe connotative and denotative meanings, and recording the results of this identification for further analysis. The results of the research show that the lyrics of the song "Sampai Jadi Debu" by Ananda Badudu contain connotative meaning and denotative meaning which are closely related to love and loyalty attached to each other. Judging from the lyrics or verses of the song, the author gives a picture of a very strong promise of loyalty and trust in a relationship until the end of life.